A glass of wine a day : daily wine tours in the Douro Valley - Campos, Filipa Maria Corrêa de Sampaio Vieira de (2022)
Wine tourism results from the junction of two sectors, wine, and tourism. Due to the fastgrowing of the internet access, tourists are choosing to go online and search for experiences beforehand and use websites such as Tripadvisor and Get Your Guide to evaluate the quality of the offers available. This study identifies the main themes and concepts related to daily wine tours experiences with the main objective of evaluating the Douro region while analyzing daily wine tours and the Food and Beverage Clusters based on reviews shared online by wine tourists. For that purpose, a qualitative approach is being developed by taking into consideration 641 reviews from ten different daily wine tours in the Douro Valley available on TripAdvisor and Get Your Guide and a conceptual analysis was elaborated using Leximancer Software where the main five themes retrieved from the online reviews were identified: “Wine”, “Tour”, “Guide”, “Trip”, “Lunch”. These themes were then divided into two clusters, Daily tour and Food & Beverages. “Wine” can be interpreted as the most important theme while “Guide” is the most important concept. Overall, there is a positive propensity in rating these experiences, having a low sample of badly rated reviews. However, there should be some improvements regarding the cruises as the results show that they create value but being sometimes “overcrowded” or “boring”. The goal of this study is to help managers understand the demand side of wine tours by developing a conceptual analysis of the narratives shared online about daily wine tours.